2009
DOI: 10.1093/brain/awp240
|View full text |Cite
|
Sign up to set email alerts
|

Off-target effects of epidermal growth factor receptor antagonists mediate retinal ganglion cell disinhibited axon growth

Abstract: Inhibition of central nervous system axon growth is reportedly mediated in part by calcium-dependent phosphorylation of axonal epidermal growth factor receptor, with local administration of the epidermal growth factor receptor kinase inhibitors AG1478 and PD168393 to an optic nerve lesion site promoting adult retinal ganglion cell axon regeneration. Here, we show that epidermal growth factor receptor was neither constitutively expressed, nor activated in optic nerve axons in our non-regenerating and regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 78 publications
2
78
2
Order By: Relevance
“…The optic nerves (ON) of anesthetised adult female 200 to 250 g Sprague-Dawley rats were exposed surgically through a supraorbital approach and crushed bilaterally 2 mm from the lamina cribrosa, using calibrated watchmaker's forceps as described by us previously. [51][52][53][54][55][56][57] Experimental Design: In Vivo Experiments…”
Section: Optic Nerve Crush (Onc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The optic nerves (ON) of anesthetised adult female 200 to 250 g Sprague-Dawley rats were exposed surgically through a supraorbital approach and crushed bilaterally 2 mm from the lamina cribrosa, using calibrated watchmaker's forceps as described by us previously. [51][52][53][54][55][56][57] Experimental Design: In Vivo Experiments…”
Section: Optic Nerve Crush (Onc)mentioning
confidence: 99%
“…For example, NGF administered to either the cell body or axon in separate Campenot chamber compartments of cultured sympathetic neurons supports survival and axon growth, but only the latter when applied to somata. 80 Similarly, application of NTF to RGC somata in vivo promotes both RGC survival and axon regeneration 51,54,55,57 and both intravitreal and intra-ON inflammation are RGC neuroprotective, but only the former promotes axon regeneration, 52 suggesting that a key RGC axon regeneration stimulatory factor is absent from the transected ON and exclusively secreted by retinal cells.…”
mentioning
confidence: 99%
“…A number of studies have confirmed that Rho and its associated signaling molecules are involved in and mediate the biological processes of axon regeneration, extension and fiber projection (28)(29)(30)(31). Rho regulates the cell actin cytoskeleton by its downstream effective factor ROCK, which is extensively involved in the biological processes of cell migration, movement, apoptosis, gene transcription and nerve regeneration (32).…”
Section: Discussionmentioning
confidence: 99%
“…These off-target effects of EGFR kinase inhibition suggest a novel therapeutic approach for the regeneration of CNS including RGC axons. 30 BDNF released from RGCs acts as a survival factor for postsynaptic neurons in retinal target fields. 31 BDNF protects RGCs from apoptosis mediated by transient ischemia through inhibition of c-Jun and caspase-2 activities.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%